1, 3, 5-Tris(phenyl-2-benzimidazole)-benzene cathode buffer layer thickness dependence in solution-processable organic solar cell based on 1, 4, 8, 11, 15, 18, 22, 25-octahexylphthalocyanine. (24th March 2015) - Banoukepa, Gilles De Roméo; Fujii, Akihiko; Shimizu, Yo; Ozaki, Masanori
Abstract: Studies on the insertion effects of a cathode buffer layer on bulk heterojunction organic solar cell based on 1, 4, 8, 11, 15, 18, 22, 25-octahexylphthalocyanine (C6PcH2 ) and 1-(3-methoxy-carbonyl)-propyl-1-1-phenyl-(6, 6)C61 (PCBM) by using 1, 3, 5-tris(phenyl-2-benzimidazole)-benzene (TPBi) as a cathode buffer layer material have been carried out. The external quantum efficiency and the short-circuit current markedly increased, resulting in the enhancement of the power conversion efficiency. The solar cell performance has been discussed from the atomic force microscopy, photoelectron yield spectroscopy and X-ray photoelectron spectroscopy measurements.